Inclusivity Discourse in Indonesian Education Policy News: A Critical Discourse Analysis of the Garuda School Program - Atika Zikri; Ngusman Abdul Manaf (SUJANA: Education and Learning Review, 2025)
This study examines how a single Kompas.com news article, "Sekolah Garuda Terbuka untuk Siswa Miskin, Inklusif, dan Tak Zonasi" (18 May 2025), constructs the discourse of inclusivity surrounding the Garuda School Program, an Indonesian government initiative introduced in 2025. Using Norman Fairclough's three-dimensional Critical Discourse Analysis model, comprising textual analysis, discursive practice, and sociocultural practice, this study analyzes lexical choice, modality, and transitivity patterns within the primary article, supplemented by related Kompas.com coverage for triangulation. Findings show that the text consistently positions the state as an active, benevolent agent and students as passive recipients, a transitivity pattern coded across eleven clauses describing the program's operation. The text relies almost exclusively on a single official source and frames the program against a discredited predecessor, producing a discursive closure that limits critical scrutiny. At the sociocultural level, the inclusivity narrative rests on a merit-based selection criterion that academic literature on meritocratic belief associates with the reproduction of structural inequality, since academic achievement correlates with unevenly distributed forms of educational and cultural capital. These findings indicate that the inclusivity narrative does not merely coexist with meritocratic selection but actively lends it public legitimacy, allowing a procedurally framed policy to be read as substantively fair. As the analysis rests on a single primary text supplemented by limited secondary sources, its findings describe this specific case rather than Indonesian educational policy journalism in general.